Optimization Of Chitosan Preparation From Crab Shell Waste - M. Djaeni (Dept. of Chemical Engineering, Diponegoro University, 2003)
Crab shell waste from seafood restaurant is potential to be used as chitosan source. This material containing 20-30% of chitin which could be converted into chitosan through deacetylation process. While, chitin could be isolated from crab shell by deproteination and demineralization. Chitosan is fine chemical used to adsorb fat from body, heavy metal adsorbent, and medicine. This research looked into the prospect of crab shell as raw material to produce chitosan. In this case, the process variable of chitosan preparation was investigated involving operation time and NaOH concentration to determine optimum condition. Whereas, the other parameters including operation temperature, NaOH to chitin ratio is respectively fixed at 70-80 0C and 5:1. As respons, the yield of chitosan is calculated. In this case, the deacetylation time is varied from 1-4 hours with the time step 1 hours and the concentration of NaOH is change from 20-50% with the step size of 10%. The results showed that the maximum yield of chitosan is 9,15%, which could be achieved at operation time of 3 hours and NaOH concentration of 20%.Keywords : crab shell, deproteination, demineralization, deacetylation, chitosan